Energy Conditions of Built-In Inflation Models in f(T) Gravitational Theories - Gamal G. L. Nashed (Advances in High Energy Physics)
We examine the validity of energy conditions of built-in inflation models in f(T) gravitational theories. For this purpose, we formulate the inequalities of energy conditions by assuming the flat and nonflat Friedmann-Robertson-Walker (FRW) universe. We find the feasible constraints on the constants of integration and evaluate their possible ranges graphically for the consistency of these energy conditions for flat, closed, and open universes. We constrain the constants of integration for flat space-time from the inflation epoch while the closed and open universe constants are constrained from late universe.